2016
DOI: 10.5056/jnm15129
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of Enhanced Asian Rome III Questionnaires in Bengali Language for Diagnosis of Functional Gastrointestinal Disorders

Abstract: Background/AimsFunctional gastrointestinal disorders (FGIDs), diagnosed by symptom-based criteria due to lack of biomarkers, need translatedvalidated questionnaires in different languages. As Bengali, the mother tongue of Bangladesh and eastern India, is the seventh most spoken language in the world, we translated and validated the Enhanced Asian Rome III questionnaire (EAR3Q) in this language. MethodsThe EAR3Q was translated in Bengali as per guideline from the Rome Foundation. The translated questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“… 9 Hindi and Bengali translated validated Enhanced Asian Rome III Questionnaires were used to collect data from the Indian and the Bangladeshi study cohorts, respectively, at inclusion and during follow‐up at 1, 3, and 6 months. 18 , 19 Data on alarm symptoms were also collected. 18 , 19 The questionnaire used to collect the data from SARS‐CoV‐2 infected patients also included data related to COVID‐19, including its severity and comorbidity.…”
Section: Methodsmentioning
confidence: 99%
“… 9 Hindi and Bengali translated validated Enhanced Asian Rome III Questionnaires were used to collect data from the Indian and the Bangladeshi study cohorts, respectively, at inclusion and during follow‐up at 1, 3, and 6 months. 18 , 19 Data on alarm symptoms were also collected. 18 , 19 The questionnaire used to collect the data from SARS‐CoV‐2 infected patients also included data related to COVID‐19, including its severity and comorbidity.…”
Section: Methodsmentioning
confidence: 99%
“…Functional anorectal pain (FARP) was diagnosed using the Rome III diagnostic criteria for functional bowel disorders [ 20 ]. A Chronic Proctalgia was diagnosed if patients exhibited chronic or recurrent rectal pain or episodic aching each lasting 20 minutes or longer for at least 6 months, with no other causes of rectal pain such as ischemia, abscess, fissure, hemorrhoids, and coccygodynia.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by the Rome Foundation-Asian working team[ 38 ] on 1805 consecutive unselected functional gastrointestinal disorder patients presenting to the primary or secondary care centers in 11 Asian centers using a culturally adapted Rome III Diagnostic Questionnaire initially translated and validated in 9 Asian languages[ 39 , 40 ] identified 9 symptom clusters by principal component factor analysis with varimax rotation. Authors concluded that though IBS and chronic constipation were the dominant symptom clusters, bowel symptom cluster with meal trigger and a gas cluster were the other prominent groups that were in line with the old Asian concept that identified epigastric localization of pain, and emphasized meal- and gas-related symptoms[ 41 ].…”
Section: Symptom Profile and Diagnosis Of Ibsmentioning
confidence: 99%